Investigating the Relationship Between Primary Malnutrition and Patient Outcomes Among Individuals Admitted to Kosar Hospital, Semnan, 2022 - Maryam Nazari; Malihe Sadeghi; Negar Adineh; Atefeh Ashabi (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Malnutrition is associated with prolonged hospitalization, delayed recovery, increased mortality among hospitalized patients, and elevated hospital costs. These outcomes can be mitigated through appropriate diagnosis and timely interventions. In this regard, the present study aimed to evaluate the nutritional status of patients aged over 19 years upon admission to Kosar Semnan Hospital. Materials and methods: In this cross-sectional study, 506 adult patients hospitalized during the first six months of 2022 at Kosar Semnan Hospital were included. After collecting demographic data and nutritional status information using a nutritional status assessment checklist, patients were screened and classified into three groups: low risk, moderate risk, and high risk for malnutrition based on predefined criteria. The data were analyzed using a significance level of P< 0.05. Results: Of the 506 patients examined, 350 (69.2%) were at risk of malnutrition upon admission. Among the participants, 49.4% were men and 50.6% were women, with a mean age of 60.9 ± 18.22 years. The risk of malnutrition at admission was low in 33.7%, moderate in 1.7%, and high in 64.9% of cases. The risk of malnutrition at admission was significantly higher among elderly patients (P<0.05) and among those hospitalized in the internal medicine ward (P<0.001). The length of hospitalization was significantly longer in patients with a high risk of malnutrition compared to those at low or moderate risk (P=0.049). In addition, the risk of mortality was significantly higher in patients classified as high risk for malnutrition (P= 0.032). Conclusion: Malnutrition was highly prevalent among hospitalized adult patients and was associated with prolonged hospital stays and increased mortality rates. Therefore, early assessment of patients' nutritional status during hospitalization, along with the implementation of appropriate nutritional interventions, is crucial to minimizing its impact on both patient outcomes and the healthcare system.